PERTANGGUNGJAWABAN INDUSTRI MEDIA DALAM MASYARAKAT TONTONAN - Rekno Sulandjari (Jurnal Ilmiah Komunikasi Makna, 2011)
Today’s free market of industry mass media isn’t quite the same as the laissez-faire approach of the robber barons of the nineteenth century because it now often is noteworthy for effi cient use of the government’s powers to support the strategies and profi ts media business. Even if public resources – such as the national forests – are thereby harmed. Given both the need for equity of access and the lack of acceptable spectacles alternatives, there seems to be no viable alternative to the mass media taking on this responsibility as fully as is necessary. Such an ethical obligation clearly stems from both the utilitarian concern for providing the greatest benefi t for the greatest number of people and emphasis on protecting the most vulnerable members of the community. It can also be argue cogently that if social responsibility means anything at all, it means fi nding a way to avoid creating a clearly defi ned group of second-class citizen in an information industry media.